After the review conference: The NPT remains robust - Jonas Schneider; Liviu Horovitz (Stiftung Wissenschaft und Politik (SWP), 2022)
Originally scheduled for 2020, the 10th Review Conference of the Treaty on the Non-Proliferation of Nuclear Weapons (NPT) had to be deferred four times. It was not until August 2022 that the 191 NPT states finally met. At least since Russia's invasion of Ukraine, observers had expected that the delegates would be unable to agree on a Final Document. Surprisingly, differences over nuclear disarmament did not play a role in the failure of the conference, despite the growing polarization over this issue since the entry into force of the Treaty on the Prohibition of Nuclear Weapons (TPNW) at the beginning of 2021. Russia alone was responsible for torpedoing the consensus. Conversely, all the non-nuclear NPT parties made major concessions in a bid to prevent the conference from failing. This shows that in a context of global tensions, nuclear disarmament is a lesser concern for the non-nuclear-weapon states (NNWS) than they themselves have long been suggesting. That the stability of the NPT does not depend on progress towards disarmament is good news. For Germany's National Security Strategy (NSS), it means that greater concessions to advocates of the TPNW are not necessary to protect the NPT.
Keywords: 320; Nuklearer Nichtverbreitungsvertrag; Vertrag über die Nichtverbreitung von Kernwaffen; Atomwaffensperrvertrag; NVV; Treaty on the Nonproliferation of Nuclear Weapons; NPT; "Nuclear Ban Treaty"; Treaty on the Prohibition of Nuclear Weapons; TPNW; Nationale Sicherheitsstrategie; NSS; Atomwaffen; Kernwaffen; atomare Abrüstung; nukleare Abrüstung; nukleare Abschreckung; Nato; Ukraine-Krieg; Ukrainekrieg; regelbasierte internationale Ordnung; nukleare Normen; nukleare Ordnung; Kernkraftwerk Saporischschja; Atomwaffenverzicht; Mittelmächte; Proliferation; Nonproliferation; Nichtverbreitung